Detection and Levels of Escherichia coli Contamination in Beef Meatballs Sold in Kota Kefamenanu District, North Central Timor Regency - Agustina Viktoria Tae; Gina Paskalia Sonia Suri; Steffanie M.C Noach (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2026)
Beef meatballs are a popular processed meat product and are highly sought after by the public due to their delicious taste, easy availability, and high nutritional value. However, this high nutritional content also makes meatballs susceptible to microbial contamination. This study aimed to detect the presence of Escherichia coli bacteria and measure the level of bacterial contamination in beef meatballs sold in Kota Kefamenanu District, North Central Timor Regency. The study used a laboratory experiment method with a purposive sampling technique on 15 beef meatball samples obtained from supermarkets and street vendors. Testing was carried out through several stages, namely initial isolation on Nutrient Agar (NA) media, cultivation on selective Eosin Methylene Blue Agar (EMBA) media, Gram staining to identify bacterial characteristics and morphology, and a Total Plate Count (TLC) test to determine the level of bacterial contamination. The results showed that all samples experienced colony growth on NA media. On EMBA media, five samples showed blackish-purple colony growth with a metallic green sheen, indicating the presence of E. coli bacteria. Gram-staining results showed pink bacteria with short, rod-shaped cells (coccobacilli) belonging to the Gram-negative bacteria group. Based on the ALT test results, four samples BK 02, BK 07, BK 09, and BK 10 had colony counts exceeding the maximum microbial contamination limit according to SNI 7388:2009, which is 5 × 101 colonies/g, and were therefore declared Not Meeting Requirements (TMS). The remaining eleven samples remained below the established threshold and were therefore safe for consumption. The conclusion of this study indicates that beef meatballs sold in Kefamenanu District are contaminated with E. coli bacteria, with most samples still meeting food safety standards. Therefore, implementing good hygiene and sanitation is essential in the processing and sales process to ensure food safety.